Effects of wood vinegar supplementation on the performance, carcass yield, intestinal histomorphology, and immune status of broiler chickens - SS Emmanuel; TC Loh; HL Foo; H Akit; MF Ab Aziz; ELT Chung (South African Journal of Animal Science, 2025)
This study aimed to determine the effects of the addition of wood vinegar (WV) to drinking water on the production performance, intestinal histomorphology, and immune response of broiler chickens. In total, 432 one-day-old chicks were allocated to six groups (T1–T6), with six replicates of 12 chicks each (72 chicks per treatment group), and raised for 35 days. Group T1 (0.0% WV) served as a negative control, group T2 (0.02% oxytetracycline) as a positive control, and groups T3 to T6 as experimental groups that received WV in their drinking water at 0.1%, 0.2%, 0.5%, and 1.0%, respectively. Data were analysed using a general linear model, and the significance of differences between the treatment groups was determined using Duncan’s multiple range test. The results demonstrated that the addition of WV to drinking water enhanced the feed conversion ratio, cumulative weight gain, and final body weight, while the abdominal fat yield was significantly decreased in the WV treatment groups. Compared to the negative control and antibiotic-treated groups, WV improved the ileum and jejunum villus height, as well as increasing plasma immunoglobulin A and M concentrations and the expression of the insulin-like growth factor-1 and growth hormone receptor genes in all the treated groups. Collectively, these results demonstrate that WV is a suitable replacement for antibiotics in broiler production, with no adverse effects on growth performance.